JEALOUSY, ABSENT OTHER CIRCUMSTANCES, DOES NOT CONSTITUTE A BASE MOTIVE (CIPEEX, 2025)
This study shows that jealousy, taken in isolation, does not constitute a base motive capable of qualifying homicide and that courts must assess the factual context and intensity of the emotion in each case. It is a descriptive-analytical, doctrinal study grounded in case-law review, distinguishing ordinary jealousy from situations in which, combined with additional elements, it may amount to a base motive. Methodologically, it examines criminal-law scholarship and decisions of Brazil’s superior courts, focusing on the reasoning used to apply or dismiss the qualifying circumstance. The findings indicate that baseness cannot be presumed from jealousy per se; to justify the qualifier, the sentiment must be linked to morally reprehensible purposes—such as revenge, possessiveness, humiliation, or instrumentalization of the victim—revealing contempt for human dignity. The study concludes that the mere presence of jealousy is insufficient to support the qualifier; a case-by-case assessment of the agent’s psychological state and the objective circumstances is required. Proper adjudication therefore depends on careful judicial reasoning and avoids generic or overly simplistic interpretations, ensuring the correct application of criminal law.